Intra-Annual Wood Formation of Cryptomeria fortunei and Cunninghamia lanceolata in Humid Subtropical China - Zheng, Zhuangpeng; Zhou, Feifei; Fonti, Patrick; Ren, Ping; Li, Xiaoxia; Miao, Guofang; Dong, Zhipeng; Fang, Keyan (Frontiers in Ecology and Evolution, 2021)
Monitoring cambial activity is important for a better understanding of the mechanisms governing xylem growth responses to climate change, providing scientific basis about tree-ring-based climate reconstructions and projections about tree growth under future climate scenarios. It plays an even more important role in investigating evergreen tree growth in regions with less distinct seasonal cycles. Subtropical evergreen forests have been studied in recent years for their sensitivity to climate change, but it remains unclear how xylem growth is driven by subtropical climates. To further understand the climate-growth response strategies of subtropical conifers, we micro-cored Cryptomeria fortunei and Cunninghamia lanceolata weekly in 2016 and 2017 at the humid subtropical Gushan Mountain in southeastern China. Our weekly growth monitoring showed that the vegetation periods of these two species were both approximately 2-3 months longer than trees in temperate and boreal forests. The growth of C. fortunei in 2016 and 2017 and C. lanceolata in 2017 showed a bimodal pattern of xylogenesis, which was induced by summer drought. The results also indicated that the earlier end of the xylem formation was related to the yearly drought stress. These findings provide more specific information about tree growth and the evidence of how climate influences wood production at the cellular level in subtropical regions.